Enhancing Banking Sector Performance: Assessing IT Capabilities with COBIT 2019 Framework Analysis - Melissa Indah Fianty (AI Society & STMIK Indonesia, 2024)
The growth of Information Technology within companies has been following its advancements. However, the unattained objectives stem from inefficient transitional systems within the company, leading to inaccurate data and project delays, consequently hindering the fulfilment of corporate expectations. This study aims to offer developmental recommendations through the assessment of IT governance capabilities. The measured capabilities reveal that objectives within processes BAI03, BAI05, and APO03 are stagnant at level 2. The findings from these processes highlight areas for improvement that can be rectified by the company. The proposed enhancements align with recommendations focusing on transitional system development and monitoring to enhance data transition efficiency, thus establishing a monitoring system to mitigate errors resulting from inefficient data transitions.